Informative Inhibiting Factors For Teachers In Implementing The Independent Curriculum At SMK Negeri 2 Sungai Penuh - Risha Febriyanti; Suharry; Nizwardi Jalinus (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The purpose of this study is to describe the factors that become obstacles in implementing the independent curriculum at SMK Negeri 2 Sungai Penuh. The method used in this study is descriptive qualitative research. The sample of this study was a subject teacher who taught in class X of SMK Negeri 2 Sungai Penuh. From the results of the study, it is known that the factos and obstacles felt by teachers consist of 3 stages, namely the planning stage, the implementation stage and the assessment stage.